CONVERSION OF OIL PALM BIOMASS TO BIO-OIL VIA SUBCRITICAL AND SUPERCRITICAL HYDROTHERMAL LIQUEFACTION - CHAN, YI HERNG (2014)
Bio-oil production from the hydrothermal liquefaction of biomass has gained attention as a promising thermochemical conversion technology in utilizing biomass as a source of renewable energy. As Malaysia is a global palm oil producer, the abundance of oil palm wastes has created a huge potential for utilization in bio-oil production. In this study, three types of oil palm biomass, namely empty fruit bunch (EFB), palm mesocarp fiber (PMF) and palm kernel shell (PKS) are liquefied using subcritical and supercritical water at various tp.mnpraturpq anH prpgS"tpr; to produce bio-oil. The optimum condition at which maximum bio-oil yield is obtained from hydrothermal liquefaction of EFB, PMF and PKS is determined and analyzed.